Lectures on Visco-Plastic Fluid Mechanics - Ovarlez, Guillaume; Hormozi, Sarah; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
The book is designed for advanced graduate students as well as postdoctoral researchers across several disciplines (e.g., mathematics, physics and engineering), as it provides them with tools and techniques that are essential in performing research on the flow problems of visco-plastic fluids. The following topics are treated: analysis of classical visco-plastic fluid models mathematical modeling of flows of visco-plastic fluids computing flows of visco-plastic fluids rheology of visco-plastic fluids and visco-plastic suspensions application of visco-plastic fluids in engineering sciences complex flows of visco-plastic fluids.
Background lectures on ideal visco-plastic fluid flows -- Viscoplastic asymptotics and other analytical methods -- Computational methods for viscoplastic fluid flows -- Rheometry of visco-plastic fluids -- Rheology of visco-plastic suspensions -- Industrial applications of yield stress fluids.
Keywords: Fluid mechanics; Continuum mechanics; Mathematical physics; Engineering Fluid Dynamics; Continuum Mechanics; Mathematical Physics